Historical imagination hermeneutics and cultural narrative - Fairfield, Paul, 1966- (Social imaginaries., 2022)
"A phenomenological and hermeneutical investigation into the nature of historical imagination. Carefully defining historical imagination, the book probes the relationship between the imaginative and the empirical, as well as the relationship between historical understanding and self-understanding"--